Aktivitas Antibakteri Propionibacterium Acnes Ekstrak Kulit Jeruk Lemon (Citrus Limon L) Pada Variasi Konsentrasi Etanol Dan Waktu Maserasi - Sukiman, Sukiman; Suwariani, Ni Putu; Anggreni, Anak Agung Made Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Lemon peel contains antibacterial compounds such as flavonoids, saponins, and essential oils. This study aims to determine the effect of ethanol concentration and maceration duration on the phenolic compound content and antibacterial activity against Propionibacterium acnes of lemon peel extract (Citrus limon L), as well as to identify the ethanol concentration and maceration duration that yield the highest levels of phenolic compounds and antibacterial activity. The study used a factorial randomized block design with two factors. The first factor was ethanol concentration, consisting of four levels: 65%, 75%, 85%, and 95%. The second factor was maceration time, consisting of three levels: 24 hours, 48 hours, and 72 hours. The data obtained were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test. The results showed that both ethanol concentration and maceration duration had a highly significant effect on total yield, total phenolic content, and antibacterial activity against Propionibacterium acnes. The interaction between treatments had a significant effect on total yield but no significant effect on total phenolic content and antibacterial activity. The ethanol concentration that resulted in the highest antibacterial activity against Propionibacterium acnes was 75%, with a clear zone of 13.52±1.00 mm, a total phenolic content of 49.29±6.57 mg GAE/g, and a yield of 19.10±0.49%. The best maceration time to produce the highest lemon peel extract was 24 hours, with a clear zone of 13.67±0.56 mm, a total phenolic content of 48.62±2.18 mg GAE/g, and a yield of 19.10±0.49%.